Clinicopathological Characteristics and Prognostic Prediction in Pseudomyxoma Peritonei Originating From Mucinous Ovarian Cancer - Fu, Fengxian; Ma, Xulan; Lu, Yiyan; Xu, Hongbin; Ma, Ruiqing (Frontiers in Oncology, 2021)
Objective: To describe the clinicopathological characteristics of mucinous ovarian cancer (MOC)-derived pseudomyxoma peritonei (PMP) and identify prognostic factors for survival. Methods: Medical records from patients with MOC-derived PMP who attended the Aerospace Center Hospital, Beijing, China between January 2009, and December 2019 were retrospectively reviewed. Survival analysis was performed with the Kaplan-Meier method, the log-rank test, and a Cox proportional hazards model. Results: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) for PMP originating from MOC were performed on 22 patients, who had a median age of 52 years at the time of surgery. At the last follow-up in June 2020, 9 (41%) patients were still alive. Median OS was 12 months (range, 1 to 102 months), and the 2-, 3- and 5-year survival rates were 23%, 9% and 5%, respectively. Conclusion: Histopathologic subtype and PCI may be applied as predictors of prognosis in patients with MOC-derived PMP. Patients with high grade disease could benefit from completeness of cytoreduction (CCR) 0/1.